Characterization of Two New brown midrib1 Mutations From an EMS-Mutagenic Maize Population for Lignocellulosic Biomass Utilization - Xiong, Wangdan; Li, Yu; Wu, Zhenying; Ma, Lichao; Liu, Yuchen; Qin, Li; Liu, Jisheng; Hu, Zhubing; Guo, Siyi; Sun, Juan; Yang, Guofeng; Chai, Maofeng; et al. (Frontiers in Plant Science, 2020)
Gene mutations linked to lignin biosynthesis are responsible for the brown midrib (bm) phenotypes. The bm mutants have a brown-reddish midrib associated with changes in lignin content and composition. Maize bm1 is caused by a mutation of the cinnamyl alcohol dehydrogenase gene ZmCAD2. Here, we generated two new bm1 mutant alleles (bm1-E1 and bm1-E2) through EMS mutagenesis, which contained a single nucleotide mutation (Zmcad2-1 and Zmcad2-2). The corresponding proteins, ZmCAD2-1 and ZmCAD2-2 were modified with Cys103Ser and Gly185Asp, which resulted in no enzymatic activity in vitro. Sequence alignment showed that CAD proteins have high similarity across plants and that Cys103 and Gly185 are conserved in higher plants. The lack of enzymatic activity when Cys103 was replaced for other amino acids indicates that Cys103 is required for its enzyme activity. Enzymatic activity of proteins encoded by CAD genes in bm1-E plants is 23-98% lower than in the wild type, which leads to lower lignin content and different lignin composition. The bm1-E mutants have higher saccharification efficiency in maize and could therefore provide new and promising breeding resources in the future.